Simultaneous observation of geomagnetic sudden commencement above and below the ionosphere - Araki, Tohru; Iyemori, Toshihiko; Kamei, Toyohisa (1985)
P(論文) A geomagnetic sudden commencement (SC) was observed by the low altitude geomagnetic satellite, MAGSAT, when it was flying very closely above a ground station (Magadan in east Siberia, geomagnetic latitude=51.1°) in a duskside (16-17h LT) meridian. The H-component at the satellite showed a positive pulse of 52nT and the D-component a negative pulse of 43nT in the beginning part of the SC. The duration of the pulse was 2-3min. The SC observed by normal-run magnetographs at Magadan and other ground stations near the satellite orbit was preceded by a typical preliminary impulse (PI) of which sense is opposite to that of the pulse observed by MAGSAT. By the use of high time resolution data from the IMS magnetometer network Alaska chain, the pulse detected by MAGSAT was identified with the PI observed at the ground stations. It was concluded that the main source current for the PI flowed between the satellite and the ground, that is, in the ionosphere, but effects of other source currents including field aligned currents should be taken into account. departmental bulletin paper